RETHINKING: HAKIKAT INTEGRITAS DALAM DUNIA PERADILAN GUNA MEWUJUDKAN PERADABAN PUBLIK DI ERA SOCIETY 5.0 - Ardhiwinda Kusumaputra (Judex Laguens, 2024)
The law is formed is to meet human needs. The existence of a judiciary with integrity is actually a bridge in actualizing law according to the needs of society. However, in reality there are still many irregularities in the administration of the justice system in Indonesia. Demonstrates an inconsistency in its integrity. This also cannot be separated from the unclear meaning of integrity from a regulatory perspective. Addressing two main problems. First, what is the nature of integrity in the world of justice as the basis for realizing public civility? Second, what are the efforts to strengthen integrity in order to create public civilization in the era of society 5.0? Clarity on the meaning of integrity is needed, especially from the perspective of legal hermeneutics. Providing an understanding of integrity as a manifestation of God's values, integrity as a public contract, and integrity as a legal consequence. Efforts to strengthen integrity can be done with a legal system approach. First, carry out regulatory arrangements, namely by providing clarity on the formulation at the level of the law regarding integrity. Second, institutional arrangements, which in this case are built on conventional and digital integration patterns. Third, directing to new habits based on a basic understanding of integrity. Aiming at the same perspective on integrity supported by conventional and digital integration.